Genome-wide analysis of Catalase gene family reveal insights into abiotic stress response mechanism in Brassica juncea and B. rapa. (May 2023) - Verma, Deepika; Kaushal, Nishant; Balhara, Rinku; Singh, Kashmir
Abstract: Environmental stresses affect the yield and productivity of Brassica crops. Catalases are important antioxidant enzymes involved in reducing excess hydrogen peroxide produced by environmental stresses. In the present study, nine and seven CAT family members in two oilseed  Brassica species ( B. juncea and B. rapa ) were identified with complete characterization based on gene and protein structure. Phylogenetic classification categorized CAT proteins into three classes and differentiated the monocot and dicot-specific CAT proteins. Further, the gene and protein characterizations revealed a high degree of conservation across the CAT family members. Differences were observed in the CAT-HEME binding affinity in CAT1, CAT2, and CAT3 isozymes, which could suggest their differential enzyme activities in different conditions. Furthermore, protein-protein interaction with other antioxidant proteins suggested their coordinated role in ROS scavenging mechanisms. Notably, the differential gene expression of BjuCATs and BraCATs and CAT enzyme activities suggested their crucial roles in major abiotic stresses faced by Brassica species. Promoter analysis in BjuCATs and BraCATs suggested the presence of abiotic-stress responsive cis- regulatory elements. Gene regulatory network analysis suggested miRNA and TF mediated stress response in BjuCATs and BraCATs. CAT family screening and characterization in Brassica sp . has established a basic ground for further functional validation in abiotic and heavy-metal stresses which can help in developing stress tolerant crops. Highlights: CAT ( Catalase) family genes play important role in abiotic stress tolerance in plants. A genome-wide analysis resulted in identification of 9 BjuCATs and 7 BraCATs, which were further classified into 3 classes. Expression analysis of BjuCATs and BraCATs suggested their roles in different abiotic stresses. Promoter and regulatory network analysis substantiated the CATs involvement in stress and other physiological responses.